2009
DOI: 10.1295/polymj.pj2009154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Structural, and Material Design of Bio-Based Polymers

Abstract: Bio-based polymers are made from bio-originated feedstocks. Among those developed thus far, polylactides (PLA) stand at the forefront of practical use and are now manufactured on a commercial scale. However, the application of PLAs has been rather limited because of their higher cost, inferior thermal and mechanical properties, and worse processability as compared to the conventional oil-based polymers. Much effort has therefore been made to address it. Our major approach is to develop a direct polycondensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…To overcome these drawbacks, many approaches have been performed, such as stereo-complexation, copolymerization, molecular design and blending with other polymers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Copolymerization of lactide with specific functional comonomers is of interest for introducing functionality into PLA chains. Louis et al 14 reported the synthesis of a copolymer of lactide and glycidol by ring-opening polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, many approaches have been performed, such as stereo-complexation, copolymerization, molecular design and blending with other polymers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Copolymerization of lactide with specific functional comonomers is of interest for introducing functionality into PLA chains. Louis et al 14 reported the synthesis of a copolymer of lactide and glycidol by ring-opening polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…117 Two synthetic approaches are available for the copolymerization: (1) ring-opening copolymerization of L-lactide with other monomers such as e-caprolactone, glycolide and depsipeptides; and (2) use of new cyclic monomers consisting of lactate and other monomer units. In the former approach, random copolymers are usually prepared and the unit compositions of the comonomers are limited to 10 mol% to retain the polymer crystallinity.…”
Section: Copolymerizationmentioning
confidence: 99%
“…Until now, several aliphatic polyesters, such as poly(lactide)s (PLA), poly(butylene succinate) (PBS), and poly(3-hydroxyalkanoate)s (PHA), have been accepted by industries as the first manufacturing products. 1 Bio-originated polyamides, polycarbonates, and acrylic polymers are now under development as next generation polymers. Among these biobased polymers, only PLAs are now manufactured on a large scale and used as plastic materials for general purposes.…”
Section: Introductionmentioning
confidence: 99%